1992
DOI: 10.1007/bf00054569
|View full text |Cite
|
Sign up to set email alerts
|

Long-term hemodynamic effects of nifedipine on congenital heart disease with eisenmenger's mechanism in children

Abstract: The hemodynamic effect of long-term nifedipine medication was studied in 10 children, 3-12 years of age, five with ventricular septal defect and five with complete atrioventricular septal defect; all had Eisenmenger's reaction, seven also had Down's syndrome. They underwent heart catheterization prior to and during 1-4 years of nifedipine therapy. Fick's principle was used to calculate the ratio of pulmonary arterial pressure to aortic pressure (PAP/PAO), the ratio of pulmonary flow to aortic flow (QP/QS), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…By definition, those patients with the true Eisenmenger syndrome are unable to fulfil the definitions of the acute responder, as described by Sitbon et al, 29 because the unrestricted defect leads to equalisation of pulmonary and systemic arterial pressures. Although an incidental study has reported a beneficial haemodynamic effect of calcium-blockade in children with the true Eisenmenger syndrome, 30 in general this therapy has not been accepted by the experts for the use in these patients.…”
Section: Current Therapiesmentioning
confidence: 99%
“…By definition, those patients with the true Eisenmenger syndrome are unable to fulfil the definitions of the acute responder, as described by Sitbon et al, 29 because the unrestricted defect leads to equalisation of pulmonary and systemic arterial pressures. Although an incidental study has reported a beneficial haemodynamic effect of calcium-blockade in children with the true Eisenmenger syndrome, 30 in general this therapy has not been accepted by the experts for the use in these patients.…”
Section: Current Therapiesmentioning
confidence: 99%
“…Studies have shown inhaled NO to reduce pulmonary vascular resistance with minimal systemic effects in patients with ES and acute pulmonary hypertensive states of other etiologies [8, 9]. Amongst these, beneficial hemodynamic effects have been anecdotally described in children with ES [10]. …”
Section: Medical Management - Study Resultsmentioning
confidence: 99%
“…22 23 Medical treatment (calcium channel entry blockers, prostacyclin) for primary pulmonary hypertension is of proven clinical benefit, [24][25][26][27][28] while the success of medical treatment in children with obstructive pulmonary hypertension remains controversial and varies with age. [29][30][31] In older patients, treatment with calcium channel entry blockers is less beneficial and this has stimulated interest in new treatments. One of these is inhalation of NO, a selective pulmonary vasodilator, which reduces the degree of pulmonary hypertension in newborn infants with persistent pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%